STIM1, ORAI1, and KDM2B in circulating tumor cells (CTCs) isolated from prostate cancer patients - Roumeliotou, Argyro; Alkahtani, Saad; Alarifi, Saud; Alkahtane, Abdullah A.; Stournaras, Christos; Kallergi, Galatea (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Previous publications have shown that STIM1, ORAI1, and KDM2B, are implicated in Ca2+ signaling and are highly expressed in various cancer subtypes including prostate cancer. They play multiple roles in cancer cell migration, invasion, and metastasis. In the current study we investigated the expression of the above biomarkers in circulating tumor cells from patients with metastatic prostate cancer. Methods: Thirty-two patients were enrolled in this study and CTCs’ isolation was performed with Ficoll density gradient. Two different triple immunofluorescence stainings were conducted with the following combination of antibodies: CK/KDM2B/CD45 and CK/STIM1/ORAI1. Slides were analyzed using VyCAP microscopy technology. Results: CTC-positive patients were detected in 41% for (CK/KDM2B/CD45) staining and in 56% for (CK/STIM1/ORAI1) staining. The (CK+/KDM2B+/CD45–) and the (CK+/STIM1+/ORAI1+) were the most frequent phenotypes as they were detected in 85% and 94% of the CTC-positive patients, respectively. Furthermore, the expression of ORAI1 and STIM1 in patients’ PBMCs was very low exhibiting them as interesting specific biomarkers for CTC detection. The (CK+/STIM1+/ORAI1+) phenotype was correlated to bone metastasis (p=0.034), while the (CK+/STIM1+/ORAI1–) to disease relapse (p=0.049). Discussion: STIM1, ORAI1, and KDM2B were overexpressed in CTCs from patients with metastatic prostate cancer. STIM1 and ORAI1 expression was related to disease recurrence and bone metastasis. Further investigation of these biomarkers in a larger cohort of patients will clarify their clinical significance for prostate cancer patients.